Implementasi Kebijakan Dana Desa dalam Pembangunan Infrastruktur Jalan Desa di Desa Sidomulyo, Kecamatan Boliyohuto, Kabupaten Gorontalo - Cindi Amelia Putri Kamana; Irawaty Igirisa; Dwi Indah Yuliani Solihin (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
This study aims to analyze the implementation of the Village Fund policy in the development of village road infrastructure in Sidomulyo Village, Boliyohuto Subdistrict, Gorontalo Regency, focusing on planning, implementation, and supervision. This study employed a qualitative, descriptive approach. Data were obtained through interviews, observation, and documentation with nine informants, including village government officials and community members. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the policy implementation has not been optimal. In the planning aspect, the process has followed formal mechanisms; however, it remains administrative and has not been based on technical needs and road condition data. In the implementation aspect, the construction process has been carried out according to the plan, yet the quality of construction has not been optimal due to limited technical capacity and the less-than-optimal application of construction standards. In the supervision aspect, the mechanism has been formally implemented but remains administrative, not technically grounded, and has not optimally involved the community.